Tamanho de parcelas e metodologias para determinaçao da produtividade em lavouras de soja e milho: para fins de seguro agrícola - Belmonte , Cristiani (2020)
The general aim of this study was to evaluate the relationship between plot size in field condition with the determination of the stand, plant height at maturation and productivity in soybean cultivated in three areas in the city of Marechal Cândido Rondon-PR; as well as determining the number of repetitions required, of different methods used to determine yield, under field conditions, and comparing the methodologies in soybean and corn crops, for agricultural insurance purposes, in areas of the city of Formosa do Oeste - PR. To determine the soybean plant stand, 18 plot sizes were tested, at plant height at maturity, 14 sizes were tested and for productivity, 10 plot sizes were tested. The measurement of the characteristics in each plot size was carried out in triplicate, being distributed at random within each area. The average of the characteristic for each plot size allowed the adjustment of two regression models, one facing upwards and the other facing downwards. At the point where the difference between the adjusted models reached the value of the sample standard deviation, the minimum ideal plot size was determined. The determinations of corn and soybean productivity were carried out in ten areas in the municipality of Formosa do Oeste. These areas were sown with seeds of the same genotype, both with corn and soybeans. Sowing took place on the same date and under similar soil, relief, water regime and management conditions. The determination of productivity was carried out using the methods: MA (Manual), CA (Bucket), LT (Litragem), BP (Weighing with Portable Scale), PC (Weighing and Classification) and the Real determination of productivity. The results obtained for each culture were tabulated and subjected to the analysis of normality and homogeneity of variance, to verify the assumptions necessary to run the analysis of variance. Subsequently, the data for each culture were subjected to joint analysis of variance, the same being characterized as a 2x6 factorial (2 years of evaluation x 6 methods for determining productivity), with each plot (area) considered as a block (repetition), totaling 10 blocks. It was verified with this work that it is necessary to evaluate 14.3 linear meters in determining the soybean plant stand. To ensure an optimal estimate of the height of soybean plants, 26 plants must be quantified. 22 m2 should be harvested to ensure an optimal estimate of soybean productivity. The methods of determining corn productivity by weighing and grading and by weighing with a portable scale generated yield estimates equal to the actual productivity of the area. The method of determining soybean productivity by weighing and grading in the year 2017/2018, by weighing and grading and by weighing with a portable scale in the year 2018/2019, generated estimates of productivity equal to the actual productivity of the area.